No es justo! = It's not fair! - Gomez, Rebecca; Collier-Morales, Roberta (New York : Scholastic Inc., 2004)
Charlie really wants to go to Mexico with Mamá for his vacation. But it's Luis and Pilar's turn to go there, instead. Charlie thinks that it's not fair! Will Charlie get to go or will he be stuck at home with nothing to do?
Keywords: Vacations -- Fiction; Spanish language materials -- Bilingual